Scientist perspectives toward the status and management of gray wolves in the western United States - Kevin R. Crooks; Mireille N. Gonzalez; Benjamin Ghasemi (Conservation Science and Practice, 2022)
Abstract To inform conservation policy, we solicited scientist perspectives on a controversial conservation issue—the US Fish and Wildlife Service status review to relist gray wolves in the western United States on the Endangered Species Act. Our survey of authors of recent scientific publications on US wolves (n = 84; 26% response rate) indicated that about two‐thirds of respondents supported relisting. About 80% disapproved of Idaho and Montana wolf management plans and believed that they pose a threat to wolf populations in the western United States. Nearly half of respondents were unsure if population estimates of wolves in Idaho and Montana were accurate and reliable and about a fifth believed they were not. Both proponents and opponents of relisting primarily offered policy‐based arguments about state versus federal management, followed by biological arguments about threats to wolves, and social and ethical arguments about wolves and their management.